2021
DOI: 10.1039/d1an00226k
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemiluminescent screening for methamphetamine metabolites

Abstract: The abuse of methamphetamine (MA) is to date detected and subsequently verified through the monitoring of MA and its metabolites within biological specimens. Current approaches require complex sample purification strategies...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…[47][48][49][50][51][52][53][54][55] This has meant typically a threshold must be established above which signals can be attributed to the presence of additional analyte species and not just those intrinsic to the biological matrix. 29,31,56 What's more, in addition to these naturally present species, additional interferents are likely to arise in the form of other illicit substances, SC are rarely found as a single species but typically contain a range of different SC structures. However, with all structures representing a controlled substance the inability to distinguish between multiple SC or indeed interference from those metabolites other than that of BB-22, will not bare a significant detriment upon this screening technique.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[47][48][49][50][51][52][53][54][55] This has meant typically a threshold must be established above which signals can be attributed to the presence of additional analyte species and not just those intrinsic to the biological matrix. 29,31,56 What's more, in addition to these naturally present species, additional interferents are likely to arise in the form of other illicit substances, SC are rarely found as a single species but typically contain a range of different SC structures. However, with all structures representing a controlled substance the inability to distinguish between multiple SC or indeed interference from those metabolites other than that of BB-22, will not bare a significant detriment upon this screening technique.…”
Section: Resultsmentioning
confidence: 99%
“…26,27 One technique shows promise for the employment as screening methodologies and has proven such in the screening of biological matrices for illicit substances is electrochemistry. [28][29][30][31][32] Electrochemistry satisfies a number of criteria implemented for the employment of sensors within the biomedical detection field. Instrumentation used for electrochemistry is now portable, electrodes disposable and operationally simple, what's more they are significantly lower in cost than spectroscopic alternatives such as Raman.…”
mentioning
confidence: 99%
“…2019 GC/MS method for fenethylline profiling of seized samples ; LC-QTOF-MS method for the simultaneous analysis of 111 amine-based compounds belonging to ergogenics, anorectics and other active components including phenethylamines (amphetamines, ephedrines), sibutramine or yohimbine [ 475 ]; excitation-emission matrix fluorescence combined with parallel factor analysis for quantitative analysis of the ATSs illegal drugs [ 476 ]; 2020 investigation of the efficiency and effectiveness of a gas-to-liquid (GTL) extraction system for the extraction of amphetamine-type substances and their precursors from the vapor phase [ 477 ]; LC-MS/MS method for detection of the presence of synthetic amines in dietary supplements [ 478 ]; enantioselective HPLC-MS/MS method for the quantification of (R)-AMP, (S)-AMP, (R)-MA, (S)-MA, (1R,2R)-pseudoephedrine, (1S,2S)-pseudoephedrine, (1R,2S)-ephedrine, (1S,2R)-ephedrine, (1R,2S)-norephedrine, (1S,2R)-norephedrine, (R)-cathinone, (S)-cathinone, and (1S,2S)-norpseudoephedrine (cathine) [ 479 ]; 2021 review of MA and AMP detection and roadside testing [ 480 ]; determination of the variations in delta C-13 and delta N-15 values of nitrogen sources used in the clandestine production of ATSs using isotope ratio mass spectrometry [ 481 ]; electrochemiluminescence strategy for the screening of MA and AMP [ 482 ]; review of laboratory-based and portable methods for detection of ATSs [ 483 ]; review of the prevalence of ATSs in Iran [ 484 ]; SALDI-MS method for the analysis of ATSs, including MA, MDMA, MDEA, and 4-fluoromethamphetamine (4-FMA) [ 485 ]; ATS drug classification using a one-dimensional convolutional neural network model [ 486 ]; 2022 colorimetric assay for detection of ATSs in aqueous solution, spiked drinks, and ‘ecstasy’ tablets [ 487 ]; development and validation of a GC-MS method for identification and quantification of AMP, MA, MDA and MDMA [ 488 ]; development of drug screening kits for the detection of ATSs in drinks [ 489 ]; analysis of feature selection method for 3D molecular structure of ATS drugs [ 490 ]; study of the pharmacological properties of MDA analogues and two related amphetamine-based compounds (N,alpha-DEPEA and DPIA) detected in street drug samples or in sport supplements [ 491 ]; chiral analysis of AMP (n = 143), MDMA (n = 94), and MA (n = 528) in samples seized in southern Germany in 2019 and 2020 using different chromatographic methods [ 492 ]; comparison of different chiral selectors for the enantiomeric determination of amphetamine-type substances by SPE-CE-MS/MS [ 493 ]; ultrahigh performance LC-MS/MS (UPLC-MS/MS) method coupled with magnetic SPE (MSPE) for determination of ultra-trace ATSs [ 494 ]; desk review of Vietnamese national drug policy documents regarding ATSs and in-depth key informant interviews were conducted from 2019 to 2021 [ 495 …”
Section: Routine and Improved Analyses Of Abused Substancesmentioning
confidence: 99%
“…Previous reports in the literature showed that the ECL signal of Ru-(bpy) 3 2+ is strongly enhanced in the presence of the proteins and amino acids which already exist in blood samples. 49,50 In this report, it was thought that this high background signal during the determination of l -Phe in the blood sample could be avoided with the proposed ECL sensor system.…”
Section: Introductionmentioning
confidence: 99%